Successful Treatment of Atlantoaxial Subluxation in an Adolescent Patient with BrachytelephalangicChondrodysplasia Punctata. (27th January 2019) - Fujimoto, Yoh; Taniguchi, Yuki; Oshima, Yasushi; Matsubayashi, Yoshitaka; Okada, Keita; Haga, Nobuhiko; Tanaka, Sakae
Abstract : Brachytelephalangic chondrodysplasia punctata (CDPX1) is characterized by brachytelephalangy and nasomaxillary hypoplasia, in addition to stippled epiphyses. Some reports have described infants with CDPX1 who exhibited cervical spinal stenosis. However, the natural course of cervical spinal lesions in this condition has not been elucidated. Here, we report a very rare adolescent case of CDPX1, which demonstrated progressive myelopathy caused by atlantoaxial subluxation and a subsequent retroodontoid pseudotumor, successfully treated with surgery. Our case highlights a new clinically important fact that upper cervical spinal lesions in CDPX1 can deteriorate even after childhood and thus need close monitoring.